Undrained shear strength of soft clay reinforce with single 16mm diameter encapsulated bottom ash column - Nabilah, Md Mashod Fakeh (2016)
Soft clay soil can be categorized as problematic soil. It consists of low shear strength, low permeability and high compressibility characteristics affect the stability and settlement of the structures constructed on this type of soil. A careful design analysis could be taken for any structure built on it. However, those characteristics could be improved through many methods and the easiest method that is being used in the construction field was stone column. On the other hand, coal is one of the world’s most important sources of energy. Disposal of bottom ash become environmental issues if it is not effectively reused or recycled for other application. This study is to present suitability in term of shear strength by using bottom ash to replace sand or granular material in column for ground improvement technique using laboratory scale model. Since sand is one of non-renewable material so by using by-product or waste material such bottom ash we can reduce the cost of construction as well as keep the non-renewable natural material in balance. Several experimental procedures are carried out to know the physical and mechanical properties of bottom ash and kaolin clay sample. Kaolin is being used as soil sample and bottom ash as the reinforced columns. The shear strength of the encapsulated bottom ash column measured by Unconfined Compression Test. A total 4 batches of kaolin sample had been tested and each batch consist of 5 specimens represent sample without bottom ash, partially penetration and fully penetration for singular bottom ash column. The specimen used were 50mm in diameter and 100mm in height. The diameter of bottom ash is 16mm and the height of the column are 60mm, 80mm and 100mm. The encapsulated bottom ash was installed at the centre of the specimen. The encapsulated bottom ash column with 10.24% area replacement ratio are 58.21%, 58.66% and 42.58% at sample penetration ratio, Hc/Hs of 0.6, 0.8 and 1.0 respectively. It can be concluded that the shear strength of soft clay could be improved by installation of encapsulated bottom ash column. However the value of shear strength of soft clay inserted with partially penetration column increased more significant compared to the fully penetration column.